Occlusal effects on text reading: an eye-tracker study - Tramonti Fantozzi, Maria Paola; De Cicco, Vincenzo; Bazzani, Andrea; Cataldo, Enrico; Bruschini, Luca; De Cicco, Davide; d’Ascanio, Paola; Faraguna, Ugo; Manzoni, Diego (Frontiers in Systems Neuroscience, 2024)
Introduction: Asymmetric electromyographic (EMG) activity during teeth clenching has been linked to cognitive impairment, as evaluated by the Spinnler-Tognoni matrices test, and to asymmetric pupil size (anisocoria). Anisocoria indicates an asymmetric Locus Coeruleus activity, leading to an asymmetric hemispheric excitability worsening cognitive performance. Bite splint wearing corrects EMG asymmetry, reduces anisocoria and improves cognitive performance. This study explores the possible effect of EMG asymmetry on oculomotor behavior during text reading. Methods: In subjects showing different degrees of EMG asymmetry during clenching, the number and duration of fixation periods during a reading task, performed under two different occlusal conditions were analyzed. The first lecture was executed with a dental impression (imprint) interposed between the dental arches (corrected condition) and the second one with the arches in direct contact (habitual condition), without clenching effort. The imprint reduced the EMG asymmetries during clenching. Results: In both occlusal conditions, total reading time correlated with duration of fixations, but not with their number. An inverse relation was observed between the number of fixations and their duration across individuals. Fixation frequency and duration were positively and negatively correlated with the amplitude of EMG asymmetry, respectively. Differently, total reading time was not related to the EMG asymmetry. When switching from the corrected to the habitual condition, an increase in the number of fixations and a reduction in their duration was observed, while total reading time could be either increased or decreased. An increased fixation frequency was observed in most of the subjects, while a reduced duration only among individuals with shorter reading times in habitual condition. Discussion: In the habitual condition, EMG asymmetry influences reading patterns (more saccades/shorter fixations, less saccades/longer fixations) in our sample. The changes in text reading behavior elicited by occlusal correction can be explained by assuming that occlusal disharmony negatively interferes with the reading task by increasing the number of saccades necessary for text scanning. This finding may also indicate an increased difficulty in processing of visual information. The potential involvement of trigeminal pathways in the relation between occlusal factors and oculomotor control is discussed.